Suitability analysis of culture area using floating cages in Ambon Bay - Tjoa, Sientje B (AQUATIC SCIENCE & MANAGEMENT, 2014)
Fish cultivation under floating net system has good and promising prospects to develop as a potential and sustainable economic activity in Ambon Bay waters due to its great coastal and marine resources potential. This study was aimed to analyze the suitability of Ambon bay waters based upon site suitability criteria matrix for floating net cage culture. For this, water quality parameters were measured and then arranged in a matrix of site suitability for floating net cage culture. Results showed that water temperature ranged from 25.3 to 26.43 â°C, current speed from 5.78 to 23.51 cm / sec,Â  depth from 5-25 m, visibilityÂ  from 4.00 to 11.00 m, salinity from 28.41 to 33.92 ppt, DO from 6.56 to 7 ppm, pH from 7.66 to 8.19, and suspended solid from 0.46 to 2.52 NTU. As conclusion, Ambon Bay waters is very appropriate for floating net cage culture development.Â Budidaya Keramba Jaring Apung memiliki prospek yang cukup cerah dan menjanjikan untuk dikembangkan menjadi suatu kegiatan ekonomi yang tangguh dan berkelanjutan di perairan Teluk Ambon, karena memiliki potensi sumberdaya pesisir dan laut yang besar. Penelitian ini bertujuan menganalisa perairan teluk Ambon untuk menentukan kesesuaian lahan berdasarkan kriteria matriks kesesuaian lahanÂ  budidaya keramba jaring apung. Untuk menentukan kesesuaian lahan budidaya keramba jaring apung di perairan TelukÂ  Ambon maka dilakukan pengukuran kualitas air kemudian disusun dalam matriks kriteria kesesuaian lahan untuk budidaya keramba jaring apung. Hasil penelitian menunjukkan bahwa suhu air berkisar dari 25,3-26,43 â°C, kecepatan arus 5,78-23,51 cm/det, kedalaman 5-25 m, kecerahan 4,00-11,00 m, salinitas 28,41-33,92 ppt, oksigen terlarut 6,56-7 ppm, pH 7,66-8,19, Muatan Padatan Tersuspensi 0,46-2,52 NTU. Sebagai kesimpulan, perairan Teluk Ambon sangat sesuai untuk dilakukan kegiatan pengembangan budidaya keramba jaring apung.